2017
DOI: 10.1111/jace.15123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structure and temperature on the thermal conductivity of molten CaO–B2O3

Abstract: The effect of the temperature and borate structure on the thermal conductivity of the molten CaO–B2O3 binary system was investigated. The thermal conductivity was measured from 1573 K to approximately the liquidus temperature using a transient hot‐wire method, and was found to decrease with increasing temperature. The temperature dependence of the thermal conductivity in the molten oxide system was interpreted in terms of the lifetime of phonon‐like excitations and Maxwell relaxation times. The short‐range ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 48 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…Of the metaborate salts, and their molten phase counterparts, sodium metaborate is that which is most studied, which is likely due to its use in certain formulations of glass [26][27][28][29][30] . To a lesser extent calcium borate, CaB 2 O 4 or CaO•B 2 O 3 , has also been studied [31][32][33] . Note that the boron in calcium metaborate has a ratio Ca to B to O ratio of 1:2:4, whereas the ratio in calcium borate, common name Gersely borate, Ca 3 (BO 3 ) 2 is 1:2/3:2.…”
Section: Resultsmentioning
confidence: 99%
“…Of the metaborate salts, and their molten phase counterparts, sodium metaborate is that which is most studied, which is likely due to its use in certain formulations of glass [26][27][28][29][30] . To a lesser extent calcium borate, CaB 2 O 4 or CaO•B 2 O 3 , has also been studied [31][32][33] . Note that the boron in calcium metaborate has a ratio Ca to B to O ratio of 1:2:4, whereas the ratio in calcium borate, common name Gersely borate, Ca 3 (BO 3 ) 2 is 1:2/3:2.…”
Section: Resultsmentioning
confidence: 99%
“…The recommended assignments of Raman peaks are summarized in Table 2 with relevant references. [14,[40][41][42][43][44][45][46][47][48][49][50][51][52][53] In the low-frequency region (between 400 and 800 cm À1 ), the deconvoluted bands were assigned to aluminate group in which peaks around 480 cm À1 were assigned to Al─F stretching vibration in AlF 6 ; peaks centered around 550 cm À1 correspond to Al─O─Al linkage, which is the major bond in the 3D aluminate network; peaks located around 770 cm À1 are related to Al─O À stretching vibration in AlO 4 units with one or two nonbridging oxygen (NBO). Among these three characteristic peaks, Al─O─Al linkage had the most prominent peak; this peak became lower with the increase in Na 2 O content, whereas Al─O À stretching vibration in AlO 4 units became higher, which came from the breakage of the Al─O─Al linkage.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…The B 2 O 3 -containing mold fluxes are studied since they are becoming the most substitution of the CaF 2 -bearing mold fluxes. [31][32][33][34] The viscosity values of two mold fluxes were measured using a rotating cylinder method. The results showed that CeO 2 decreased the viscosity values of two mold fluxes, but increased the break temperature of the CaF 2 -bearing mold fluxes sharply.…”
Section: Effects Of Ceo 2 On Melting Temperature Viscosity and Strumentioning
confidence: 99%